A retreat critique: Deliberations on design and ethics in the flood zone. Issue 3 (2nd September 2019) - Yarina, Lizzie; Mazereeuw, Miho; Ovalles, Larisa
Abstract: Climate change is increasingly making areas of our planet difficult or dangerous to inhabit. 'Managed retreat', the intentional relocation of settlements away from hazardous zones, is growing as a proposed strategy for adapting to climate change in the United States and around the globe. As designers begin to integrate retreat into their toolkit of adaptation strategies, and as they are asked to participate in projects that include managed retreat, it is important that they also understand and negotiate the social, political and environmental implications of this form of climate adaptation. Retreat projects are often fraught with equity issues: who should relocate? And who should decide? Puerto Rico, which has a long history of displacement due to purported environmental risk, and which is currently the site of new retreat proposals as a result of Hurricane Maria's destruction, provides a space for analysing retreat projects and policies, and the role of spatial designers in their design and implementation.